Mineral Composition of Litter in Commercial Broiler Houses - Miles , Dana M.; Brooks, John P.; Moore, Philip A. (International Journal of Poultry Science, 2018)
Objective: The overall aim was to assess mineral content of broiler litter originating from U.S. commercial broiler houses and to determine how mineral content varies with season, as well as location within houses. Materials and Methods: Over a period of 4 years, approximately 1100 litter samples were collected in a grid pattern within four U.S. commercial broiler houses. The sources of variation, on which analysis of variance was based, included season (winter vs. summer), bird age (placement, mid-flock, market) and location within the house (across, lengthwise). Results: The range of concentrations for the primary minerals was (g kg–1): Ca 23.7±8.6, K 35.4±9.1, Mg 8.1±2.4, Na 10.9±3.3 and P 16.6±4.6. The secondary minerals were in the range of (mg kg–1): Cu 730±360, Fe 1120±560, Mn 730±216 and Zn 550±150. Summer mineral content was greater at all sampling ages. At market age, mineral concentrations were greater in the cooling pad and brood areas but least near the fans. Litter minerals were greater near walls when compared to the center of houses. Conclusion: Half-house brooding explained the greater concentrations in the cooling pad and brood areas. Heavy cake in the fan area had distinct properties compared to litter elsewhere in the houses. Trends in mineral composition of broiler litter complemented known management practices related to brooding (half-house) and phase feeding (reduction in levels during growth period).